Antifungal effects and active compounds of the leaf of Allium mongolicum Regel - Qu, Huan; Guo, Zhen; Ma, Li; Zhang, Xiu; Ma, Haijun; Chen, Yang (Frontiers in Chemistry, 2022)
Taking plant metabolites as material to develop new biological fungicides is still an important mission for pesticide development, and the preliminary study confirmed that Allium mongolicum showed a certain inhibitory effect on plant pathogens. In this study, the antifungal activity of extracts of Allium mongolicum was studied and the compounds were isolated, purified and identified by HPLC, NMR and ESI-MS. The methanol extract of Allium Mongolicum exhibited certain inhibitory activity against almost all nine tested pathogens at concentration of 0.5 mg/mL. Sixteen compounds were isolated and purified from the extract, which were identified as nine flavonoids, six phenolic acids and an amino acid. Among them, cinnamic acid derivatives1, 2, 3, flavonoids 7, 8, 9 and 13 and threonine were separated in Allium Mongolicum for the first time.